TANGGUNGJAWAB FORMIL DAN MATERIL BENDAHARA PENGELUARAN PEMBANTU DALAM GANTI KERUGIAN KEUANGAN NEGARA PADA PERKARA TINDAK PIDANA KORUPSI - Permana, Cokorda Dian (Universitas Tadulako, 2020)
Assistant Expenditure Treasurer is a person who is appointed to assist the Expenditure Treasurer to carry out payments to those entitled to the smooth implementation of certain activities. Therefore, any irregularities in the management of State finances caused by acts of violation of law or negligence must be replaced by the guilty party, and processed with criminal charges as criminal acts of corruption. How is the Treasurer's Formal And Material Responsibility Expenditures and/or Treasurer Assistant Expenditures when committing fraud or I rregularities in the financial management of the State/Region which results in financial loss to the State/ Region, how to settle State Financial Compensation, if the Treasurer of Expenditures and Treasurers law or negligence in financial management which results in adverse State/Regional finance, in terms of material and/or formal accountability. The approach used in this research was the conceptual approach, which starts from the issue that accountability for managing state finances is known as formal accountability or material, but the definition of material and material responsibilities is not given in detail. What is the opinion of the experts, and what about the legislation that applies in accordance with the management of State finances. Based on the nature of this research that used descriptive research, the analysis used was content analysis. Content Analysis according to experts that there are three conditions: Objectivity, Systematic Approach, and Generalization.The formal and material responsibility of the Expenditure Treasurer or Assistant Expenditure Treasurer in the case of making a mistake due to fraud and overusing authority, which results in state losses, the Expenditure Treasurer/ Assistant Expenditure Treasurer can be sued and threatened with crimes in accordance with the Corruption Act. Besides that, it can also be threatened with compensation. And can be subject to the laws of the State Administration, the Civil Code. What is the loss of the State due to the misconduct/negligence of the management of State finances by the Expenditure Treasurer/Assistant Expenditure Treasurer. Because there is a difference in the lack of inventory money between physical and bookkeeping and cannot be explained, which means the Expenditure Treasurer/Assistant Expenditure has made a mistake in managing inventory money. To return losses to the State, the Expenditure Treasurer/Assistant Expenditure Treasurer may be required to compensate the State for the recovery of state finances.again at regulation, but at the creativities of upholder apparatus law which able to actualize law in space and time with precisely.